The university: title factory? (Journal of Parents and Teachers, 1995)
Today's university is criticized for its focus on mediocrity and degree attainment, rather than fostering critical thinking and personal growth. An education that promotes didactics and self-knowledge, rather than a system that perpetuates conformity, is advocated. The need for profound social and educational change is essential to overcome current limitations.
Keywords: mediocrity; critical thinking; growth; change